Declining Childhood and Adolescent Cancer Mortality - Smith, Malcolm A. (2014)
PURPOSE: To evaluate whether progress continues in identifying more effective treatments for children and adolescents with cancer, we examined overall as well as disease-specific childhood cancer mortality rates for the United States, focusing on data for 2000–2010. METHODS: Age-adjusted United States mortality trends for 1975 to 2010 were estimated using joinpoint regression analysis. Analyses of annual percentage change (APC) were performed on the same diagnostic groupings for the time period restricted to 2000–2010 for < 20, < 15 and 15–19 year age groupings. RESULTS: Following a plateau in mortality rates from 1998–2002 (APC = 0.3), the annual decline in childhood cancer mortality for 2002–2010 (−2.4%) was similar to that observed from 1975 to 1998 (−2.7%). Statistically significant declines in mortality rates for 2000–2010 were noted for acute lymphoblastic leukemia, acute myeloid leukemia, non-Hodgkin lymphoma, Hodgkin lymphoma, neuroblastoma, CNS cancers, and gonadal cancers. For 2000–2010, the rates of decline in mortality for the 15–19 year group were generally equal to or greater than those of the 0–14 year group. Improvements in treatment since 1975 resulted in over 45,000 cancer deaths averted through 2010. CONCLUSIONS: Cancer mortality for both children and adolescents declined from 2000–2010, with significant declines observed for multiple cancer types. However, over 1900 cancer deaths still occur each year among children and adolescents in the United States, and many survivors experience long-term effects that limit their quality of life. Continued research directed towards identifying more effective treatments that produce fewer long-term sequelae is critical to address these remaining challenges.